Sudinians on the Amber Road or the Amber Road of the Sudinians? - Jovaiša, Eugenijus (Archaeologia Lituana, 2025)
The article examines the ‘Sudinians’ mentioned in Roman sources of the 2nd century AD. Claudius Ptolemy, in his Geography, referred to this Baltic tribe – the Sudinians – twice in total: once in European Sarmatia, and once in Greater Germania. The location of the former has always been within the familiar environment of the eastern Masurian lake district. The latter, the Sudinians of Greater Germania, were ‘placed’ by Ptolemy near the Danube River. Although Lithuanian scholars have been aware of this, it has not been investigated in depth. Based on data from various disciplines, the article analyses whether the Sudinians mentioned by Ptolemy could have actually lived in the location he indicated, and whether there are cultural connections with the Danubian Antiquity, with the ‘northern’ Sudinians, and with other Aestian tribes.